2015
DOI: 10.14442/jgfm.16.3_170
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Link between Diabetes and Cancer

Abstract: It has been suggested that diabetes mellitus is associated with an increased risk of cancer. Epidemiological data in Japan demonstrate that diabetes is associated with increased risk for total cancers and site‐specific cancers at colorectum, liver, and pancreas. Insulin resistance with subsequent hyperinsulinemia is the most frequently proposed hypothesis to explain this link. In addition, several facets of lifestyle including obesity, smoking, and lack of exercise, and treatment for diabetes may also affect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…A growing body of evidence has shown that type 2 diabetes is associated with an increased risk of total cancer death and total cancer incidence, including cancers of the liver, endometrium, pancreas, kidney, colorectal, bladder and breast. Of interest, the risk of prostate cancer is significantly decreased.…”
Section: Cancer Risk In Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence has shown that type 2 diabetes is associated with an increased risk of total cancer death and total cancer incidence, including cancers of the liver, endometrium, pancreas, kidney, colorectal, bladder and breast. Of interest, the risk of prostate cancer is significantly decreased.…”
Section: Cancer Risk In Diabetesmentioning
confidence: 99%
“…Of note, it was speculated for a certain period of time that insulin formulation might increase the risk of cancer. Current evidence on the risk of cancer in association with any diabetes treatment to prove the causal relationship between those medications and cancer is limited because of their inadequate adjustment for confounders, not accounting for the degree of exposure to drugs and their short follow‐up periods.…”
Section: Cancer Risk In Diabetesmentioning
confidence: 99%